Challenges and opportunities for informational societies from the present to become reliable learning and knowledge societies - Eduardo ROMERO SÁNCHEZ; Marta GUTIÉRREZ SÁNCHEZ (Ediciones Universidad de Salamanca, 2013)
This article pretend to describe the principal social trends and cultural features that prevail today, too look the philosophical foundation of thinking, feel , living and to give an educative  response and accepted to the axiological reality  and cultural present. In modern western societies great paradoxes and contradictions coexist: economical growth, technological development and greater dimensions of freedom, but also great consumption, cultural deterioration, technological dependence and unique thought. Given this we talk about the great possibilities and at the same time of the terrible threats that exist in that modern information societies. In order to become acquainted with this reality, we have focused the analysis in 3 key aspects: the impact of digital devolution, the condition of culture in contemporary society, and the need of a "new education".